Trastorno de estrés postraumático de los participantes en acciones militares - Heorhii Chernyshov (Universidad Hemisferios, 2020)
The article is devoted to the study of the problem of post-traumatic stress disorder (PTSD) of combats in the context of the protection of human rights. Methods used in this research are theoretical and empirical, with an anonymous survey of 212 participants in the fighting in the East of Ukraine. Attention is focused on the fact that PTSD is a complex problem, the negative consequences of which are studied in the framework of sociology, criminology, and criminal proceedings, as well as psychology, psychiatry, medicine in general. The article discusses the features of post-traumatic stress disorder of combats in the east of Ukraine. The conclusions are formulated on the main social problems of war veterans in Ukraine and ways to solve them. It has been established that persons who took part in hostilities in the east of Ukraine have a number of social problems after returning from the conflict zone, because of which individuals cannot fully exercise their constitutional rights. A potential “risk group” is defined in the article among war veterans who are in greater need of social and governmental patronage. In addition, it formulates specific proposals to minimize the possible negative consequences of participation in hostilities, as well as to protect constitutional rights, establish social policies and support war veterans.